Prognose do diâmetro e da altura de árvores individuais utilizando inteligência artificial - Vieira, Giovanni Correia (2015)
The models are composed of individual trees submodels estimating generally competition, mortality and growth height and diameter of each tree. Are usually adopted when you want the best detailed information to estimate forest multiproducts. In these models, estimates of growth in diameter at 1.30 m above the ground (DBH) and total height (H) is obtained by regression analysis. Recently, artificial intelligence techniques are being used with good performance in forest measurement. Therefore, the aim of this study was to evaluate the performance of artificial intelligence techniques (artificial neural networks and neuro-fuzzy systems) to estimate the growth in DAP and height of eucalyptus trees. We used continuous data eucalyptus forest inventories annually measurements DAP total height of the first 15 trees and dominant height of the portion, according to the concept of Assmann (1970), 398 parts. The database was divided into 70% of the plots for the training of artificial neural networks and neuro-fuzzy system; 15% of the plots for the cross-validation; and 15% of the plots for validating systems. Based on the results, it was noted that the independent competition index of distance 5 - IID5 proposed by Glover; Hool (1979), was the one that had the highest correlation with the age, growth in DAP and height. It was observed that the artificial intelligence techniques showed good accuracy in estimating the growth in DBH and total height. The two techniques discussed can be used for prognosis and overall height of DAP.